2019
DOI: 10.4187/respcare.06447
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Respiratory Therapist-Driven Continuous Albuterol Weaning Protocol in the Pediatric ICU

Abstract: BACKGROUND: Status asthmaticus is one of the most frequent admission diagnoses in the pediatric ICU (PICU). Collaboration between respiratory therapists (RTs) and physicians may help efficiently deliver care to a patient in status asthmaticus. The Pediatric Asthma Severity Score (PASS) is a measure of severity of a patient's asthma exacerbation at a point in time. The aim of this quality improvement initiative was to establish an RT-driven continuous albuterol weaning protocol using the PASS score. We hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…We believe that the key components for a successful RT-driven management protocol are based on the following: (1) involving inter-professional team members in analyzing failure modes and establishing the protocol; (2) integration of the protocol in EMR, which improves the communication of protocol adherence between team members; (3) conducting education before implementation of the protocol; (4) frequent audits for protocol compliance, providing team members with feedback and reeducation when needed, and (5) modifying the protocol to reach the project's goals. 14,15 HFNC is becoming first-line therapy in many PICUs to treat patients with bronchiolitis. Standardized clinical pathways have consistently demonstrated cost effectiveness and improved patient outcomes, 21,22 yet there are no standards for HFNC management of patients with bronchiolitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the key components for a successful RT-driven management protocol are based on the following: (1) involving inter-professional team members in analyzing failure modes and establishing the protocol; (2) integration of the protocol in EMR, which improves the communication of protocol adherence between team members; (3) conducting education before implementation of the protocol; (4) frequent audits for protocol compliance, providing team members with feedback and reeducation when needed, and (5) modifying the protocol to reach the project's goals. 14,15 HFNC is becoming first-line therapy in many PICUs to treat patients with bronchiolitis. Standardized clinical pathways have consistently demonstrated cost effectiveness and improved patient outcomes, 21,22 yet there are no standards for HFNC management of patients with bronchiolitis.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Previous studies have reported that the implementation of inter-professional quality improvement initiatives not only improved subjects' clinical outcomes and increased RT satisfaction, but also did not lead to an increase in adverse events. 14,15 The aim of this quality improvement project was to decrease the duration of HFNC in the PICU via a standardized RT-driven HFNC management protocol.…”
Section: Introductionmentioning
confidence: 99%
“…As modern health care provides increasing numbers and varieties of diagnostic tests and therapeutic interventions, there is also increasing risk of overuse. 19 Overuse of INO is not only an expensive waste of hospital resources, but it may also adversely impact patient outcomes. Our goal was not to limit the amount of medication provided to patients who required or benefited from INO, but to decrease the amount provided to patients who no longer needed it.…”
Section: Discussionmentioning
confidence: 99%
“…Maue et al 8 hypothesized that implementation of a continuous albuterol weaning protocol based on the Pediatric Asthma Severity Score (PASS) 9 would decrease albuterol usage without increasing adverse events. The authors did not report a decrease in albuterol usage after implementation of the protocol (P > .99), although adverse events also did not increase (P > .99).…”
Section: Year In Review: Asthmamentioning
confidence: 99%
“…However, their RT staff reported a significant increase in involvement in patient care management decisions, speed of continuous albuterol weaning, and RT input in continuous weaning (P < .01; Table 2). 8 Miller et al 10 conducted a similar study, hypothesizing that implementation of an asthma care protocol based on the Modified Pulmonary Index Score 11 would result in a decrease in total hospital length of stay (LOS), decrease in pediatric ICU LOS, and albuterol usage. They reported a decrease in all 3 of these outcomes (P < .003), as well as a significant increase in the use of high-flow nasal cannula (P < .001) and noninvasive ventilation (P < .02) after implementation of the protocol and a decrease in average subject heart rate (P < .006) and breathing frequency (P < .006) at admission ( Table 3).…”
Section: Year In Review: Asthmamentioning
confidence: 99%